Selenium compounds for cancer prevention and therapy – human clinical trial considerations - Lü Junxuan; Jiang Cheng; Hu Hongbo (Medical Review, 2025)
Selenium (Se) is an essential trace mineral crucial for human health. Nearly a dozen human clinical trials with seleno-methionine (SeMet) and selenized-yeast (contains mostly SeMet) for the prevention of non-cutaneous solid organ cancers in North America and European countries conclusively refuted their utility. We have articulated two lessons from these trials: (1) the anti-oxidant hypothesis was tested in inappropriate Se-adequate populations, and (2) the selection of these Se forms was not supported by cell culture and animal efficacy data. Nevertheless, preclinical studies of proximal methylselenol precursors (“methyl Se”) have shown many desirable attributes, involving crucial molecules and pathways in cancer epithelial cells, vascular endothelial, immune and inflammatory cells in the tumor microenvironment, for potential use as chemopreventive and therapy agents. Methylseleninic acid and Se-methylselenocysteine are prototypical methyl-Se, yet not equal in their targets. Selenate, selenite and selenious acid had been recently studied in human clinical trials, providing novel safety data, but, missing critical genotoxicity assessments. Given the popularity of Se-enriched foods in China and a continued presence of nutritional Se deficiency in many localities, we discuss recommendations for clinical studies of Se forms for cancer therapy or chemoprevention in China and other countries with similar Se nutrition predicament.